Students Perception of Factors Affecting Fluency During Speaking Performance in Higher Education Student - utomo, budi (RETAIN, 2022)
This study identifies factors affecting fluency during speaking performance in higher education student at State University of Surabaya. The students in the debate class are still not fluent and confidence to speak. Therefore, the researcher decided to take this study that identify and describe the challenges during speaking performance. This research is aimed as a reference for the educators to decide the best way to overcome speaking challenges in the class especially in debate class. The research design is qualitative that uses questionnaire and interview as the instrument. The questionnaire distributed to 65 participants and 4 participants were interviewed. This study found that there are several internal and external factors affecting students’ performance in speaking class. Some of the tips are served, those are from the students’ strategies who got the high score in debate class. This study is expected to contribute to the body knowledge and as a reference for the future researchers in the same study field.